2015
DOI: 10.1177/2156587215604073
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Chiropractic

Abstract: We assessed the attitudes of Canadian obstetricians toward chiropractic with a 38-item cross-sectional survey. Ninety-one obstetricians completed the survey, for a response rate of 14% (91 of 659). Overall, 30% of respondents held positive views toward chiropractic, 37% were neutral, and 33% reported negative views. Most (77%) reported that chiropractic care was effective for some musculoskeletal complaints, but 74% disagreed that chiropractic had a role in treatment of non-musculoskeletal conditions. Forty pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Through the lens of a qualitative study designed to inform an upcoming chiropractic integration process, these results extend what is known about the perceived value and role of chiropractors within medical settings. While the lay public and chiropractic patients report fairly favorable assessments of chiropractic [ 5 , 7 , 10 , 44 ], clinician attitudes often pitch toward more neutral or even negative views [ 3 , 19 , 22 , 23 ]. The current study found generally positive support for the addition of a chiropractor to a specific clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the lens of a qualitative study designed to inform an upcoming chiropractic integration process, these results extend what is known about the perceived value and role of chiropractors within medical settings. While the lay public and chiropractic patients report fairly favorable assessments of chiropractic [ 5 , 7 , 10 , 44 ], clinician attitudes often pitch toward more neutral or even negative views [ 3 , 19 , 22 , 23 ]. The current study found generally positive support for the addition of a chiropractor to a specific clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the literature on interactions between chiropractors and other healthcare professionals often tells a story of fragmentation, disconnection, boundary skirmishes, and a general failure to communicate [ 12 17 ]. Primary care providers and medical specialists have recognized the competence of some chiropractors to treat some musculoskeletal problems in some patients, particularly those with low back pain [ 18 , 19 ]. Medical and osteopathic physicians, physiotherapists, manual therapists, obstetricians and midwives, and other healthcare professionals often report minimal knowledge of the chiropractic profession or its treatments [ 18 20 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of diversity within the daily practice of chiropractic,9, 25, 29 including whether there is an evidence-based grounding of the practice 25, 28…”
Section: Barriers To Patient Referralmentioning
confidence: 99%
“…However, the general public 24 and referring health care providers as a group25, 28 remain wary. They cite skepticism for extensive treatment plans and claims of efficacy in nonmusculoskeletal conditions,28, 42, 49 as well as the promotion, by some, of pseudoscientific stands on health practices 6, 46, 52, 53, 54. Skepticism extends to the reliance by some DCs on the as yet scientifically undefined concept of “subluxation” as the sole grounds for providing care 6, 55.…”
Section: Divergent Identity Formationmentioning
confidence: 99%